Spunbond nonwoven fabrics and laminated nonwoven fabrics, methods for manufacturing the same, and sanitary materials
The use of crimped composite fibers with a propylene-based polymer and copolymerized α-olefin, along with an elastomer layer, addresses the flexibility and strength issues in spunbond nonwoven fabrics, ensuring excellent performance in sanitary materials.
Patent Information
- Application Number
- KR1020237028428
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-18
- Filing Date
- 2022-03-10
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-03-10
AI Technical Summary
Existing spunbond nonwoven fabrics lack sufficient bending flexibility and mechanical strength, particularly when used in sanitary materials, due to inadequate fiber crimp structure and uneven weight distribution caused by heat treatment, which is exacerbated in thin fabrics.
A spunbond nonwoven fabric composed of crimped composite fibers with a propylene-based polymer as the main component and a propylene-based copolymer formed by copolymerizing an α-olefin, where the second component is positioned at the innermost side of the crimp, and the orientation parameter of the second component is 5.0 or higher, along with a laminated nonwoven fabric incorporating an elastomer layer.
The solution achieves a nonwoven fabric with enhanced bending flexibility and mechanical strength suitable for sanitary materials, maintaining uniform weight distribution and preventing strength reduction.
Smart Images

Figure 112023092138697-PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a spunbond nonwoven fabric having excellent bending flexibility and being particularly desirable for use as a sanitary material, and a laminated nonwoven fabric having at least one elastomer layer laminated thereon. Background Technology
[0002] Recently, there has been an increasing demand for improved wearing comfort in hygiene materials such as disposable diapers and sanitary pads. Particularly for materials covering the lumbar and gluteal regions, since a tight fit to the body's contours is preferred, there is a demand for improved bending flexibility in the non-woven fabric materials used.
[0003] Conventionally, polypropylene spunbond nonwoven fabrics composed of straight fibers have been widely used in such areas. However, because the fibers constituting the polypropylene spunbond nonwoven fabric themselves lack elasticity, the bending flexibility was insufficient as the fibers held in place between the heat-fusion points when the sheet was bent.
[0004] Regarding this problem, Patent Document 1 proposes a nonwoven fabric of crimped composite fibers composed of two types of propylene-based polymer components. Additionally, Patent Document 2 proposes a method for manufacturing a spunbond coloft nonwoven web by performing a specific pre-consolidation treatment on a nonwoven web comprising a crimped multi-component fiber composed of a polypropylene homopolymer and a copolymer of polypropylene and polyethylene.
[0005] In addition, Patent Document 3 proposes a nonwoven fabric in which a composite fiber in which multiple resins with different thermal shrinkage rates form a phase structure is heat-treated to produce fine crimps. Prior art literature
[0006] Japanese Patent Publication No. 2007-308868 Japanese Patent Publication No. 2018-024965 Japanese Patent Publication No. 2012-012758 The problem to be solved
[0007] In spunbond nonwoven fabrics, when a spring-like crimp structure is formed in the fibers, excellent bending flexibility is obtained because the fiber crimp structure can stretch gently when the sheet is bent. Furthermore, this effect can be enhanced as the fiber crimp structure within the nonwoven fabric becomes finer—that is, as the spacing between adjacent crimp crests becomes smaller and the room for fiber elongation becomes sufficiently large.
[0008] In the technology of Patent Document 1, crimping is induced in the fiber by keeping the melting point difference of two propylene-based polymer components and the ratio of composite components within a specified range. In addition, in the technology of Patent Document 2, crimping is induced in the fiber by using specified raw materials and performing a specific pre-consolidation treatment. However, since these technologies cannot make the crimp structure of the fiber sufficiently fine, excellent bending flexibility cannot be obtained as a result.
[0009] On the other hand, the technology of Patent Document 3 promotes the development of fiber crimp by performing heat treatment on the nonwoven fabric, thereby enabling the acquisition of fine crimp. However, since heat treatment is indispensable for achieving an ideal crimp shape, uneven weight distribution per unit area within the nonwoven fabric surface is prone to occur during heat treatment, resulting in inferior mechanical strength. In particular, for thin nonwoven fabrics (approximately 100 g / m² or less) used as sanitary materials, the reduction in strength due to such uneven weight distribution per unit area is more pronounced, making it undesirable. Furthermore, since the technology of Patent Document 3 is essentially a polyester-based nonwoven fabric, adhesion to polypropylene spunbond nonwoven fabrics, which are widely used as sanitary materials, becomes a significant challenge.
[0010] Therefore, the objective of the present invention is to provide a spunbond nonwoven fabric and a laminated nonwoven fabric that can achieve excellent bending flexibility for use as a nonwoven fabric for hygiene products without compromising mechanical strength, taking into account the above circumstances. means of solving the problem
[0011] As a result of repeated careful consideration to achieve the above objective, the inventors have obtained the finding that by using specific raw materials in the crimped composite fibers constituting the spunbond nonwoven fabric and controlling their molecular orientation, a spunbond nonwoven fabric having excellent bending flexibility for use as a nonwoven fabric for hygiene products can be obtained without compromising mechanical strength.
[0012] The present invention has been completed based on these findings, and according to the present invention, the following invention is provided.
[0013] The spunbond nonwoven fabric of the present invention is a spunbond nonwoven fabric composed of a crimped composite fiber comprising a first component having a propylene-based polymer as the main component and a second component having a propylene-based copolymer formed by copolymerizing an α-olefin, wherein in the cross-section of the crimped composite fiber, the second component is disposed at the innermost side of the crimp, and the orientation parameter (I2) of the second component is 5.0 or higher.
[0014] According to a preferred embodiment of the spunbond nonwoven fabric of the present invention, the propylene-based polymer of the first component is a propylene homopolymer, and the orientation parameter (I1) of the first component is 6.0 or less.
[0015] According to a preferred embodiment of the spunbond nonwoven fabric of the present invention, the area ratio of the second component in the cross-section of the crimped composite fiber is 1 to 80%.
[0016] According to a preferred embodiment of the spunbond nonwoven fabric of the present invention, the number of crimps of the crimped composite fibers observed on the surface of the nonwoven fabric is 50 / 25 mm or more.
[0017] And, the laminated nonwoven fabric of the present invention is formed by laminating a spunbond nonwoven fabric layer made of the spunbond nonwoven fabric and at least one elastomer layer.
[0018] According to a preferred embodiment of the laminated nonwoven fabric of the present invention, the elastomer layer is a layer made of an elastomer nonwoven fabric.
[0019] The sanitary material of the present invention is composed of at least a portion of the spunbond nonwoven fabric or the laminated nonwoven fabric.
[0020] In addition, the method for manufacturing a spunbond nonwoven fabric according to the present invention preferably involves separately melting the first component and the second component, which has a melt viscosity at least 1.20 times higher than that of the first component, and then extruding a composite polymer from a composite spinneret, and then forming a crimp such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt to form the crimped composite fiber, and collecting the crimped composite fiber on the collection belt.
[0021] According to a preferred embodiment of the method for manufacturing a spunbond nonwoven fabric of the present invention, a composite polymer having a mass ratio of 20:80 to 99:1 of the first component and the second component is extruded.
[0022] In addition, the method for manufacturing a laminated nonwoven fabric of the present invention preferably comprises the steps of: separately melting the first component and the second component having a melt viscosity at least 1.20 times higher than that of the first component; extruding a composite polymer from a composite spinneret; forming a crimped composite fiber by forming a crimp such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt; collecting the crimped composite fiber on a collection belt to form a spunbond nonwoven fabric layer; and laminating at least one elastomer layer.
[0023] According to a preferred embodiment of the method for manufacturing a laminated nonwoven fabric of the present invention, the elastomer layer is formed by the spunbond method.
[0024] According to a preferred embodiment of the method for manufacturing a laminated nonwoven fabric of the present invention, the elastomer layer is formed by a melt-blow method. Effects of the invention
[0025] According to the present invention, a spunbond nonwoven fabric capable of achieving sufficient strength and excellent bending flexibility for use as a nonwoven fabric for sanitary materials, and a laminated nonwoven fabric having at least one elastomer layer laminated thereon can be obtained. Brief explanation of the drawing
[0026] FIG. 1 is a schematic side view of a crimped composite fiber as seen when observed with a scanning electron microscope (SEM) or the like, where FIG. 1A is a side-by-side type composite fiber and FIG. 1B is a schematic side view of an eccentric sheath-core type composite fiber. FIG. 2 is a diagram illustrating a method for measuring the crimp diameter in a scanning electron microscope (SEM) image observing the surface of an example of a spunbond nonwoven fabric according to the present invention. Specific details for implementing the invention
[0027] The spunbond nonwoven fabric of the present invention is a spunbond nonwoven fabric composed of a crimped composite fiber comprising a first component having a propylene-based polymer as the main component and a second component having a propylene-based copolymer formed by copolymerizing an α-olefin, wherein in the cross-section of the crimped composite fiber, the second component is disposed at the innermost side of the crimp and the orientation parameter (I2) of the second component is 5.0 or higher. The components thereof will be described in detail below, but the present invention is not limited in the slightest to the scope described below, as long as it does not deviate from the gist thereof.
[0028] [Propylene-based polymer]
[0029] First, the propylene-based polymer of the spunbond nonwoven fabric of the present invention refers to a polymer having propylene as the main structural unit component. Examples of such propylene-based polymers include propylene homopolymers, or copolymers having propylene as the main structural unit component and one or more types of α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, and 4-methyl-1-hexene. The "propylene as the main structural unit component" referred to herein typically means that the main chain structure of polypropylene is included in an amount of 80 mass% or more in each polymer component constituting the crimped composite fiber. Furthermore, the above propylene-based polymer may include other propylene-based polymers or ethylene-based polymers. In addition, the above-mentioned propylene-based polymer may include various additives such as inorganic materials like titanium oxide, silica, and barium oxide, carbon black, coloring agents such as dyes or pigments, flame retardants, fluorescent whitening agents, antioxidants, or ultraviolet absorbers.
[0030] In the spunbond nonwoven fabric of the present invention, by using a crimped composite fiber made mainly of a propylene-based polymer, adhesion to other materials can be improved when used as a sanitary material.
[0031] In addition, the “main component” referred to in the present invention is typically a component that accounts for 80 mass% or more of each polymer component constituting each component crimped composite fiber.
[0032] In the propylene-based polymer according to the present invention, it is preferable that at least a portion thereof contains a fatty acid amide compound. By making the content of the fatty acid amide compound preferably 0.5 mass% or more, more preferably 0.7 mass% or more, and even more preferably 1.0 mass% or more, the fatty acid amide compound acts as a lubricant on the fiber surface, thereby enabling the production of a spunbond nonwoven fabric with excellent tactile properties. Furthermore, although the upper limit of the content of the fatty acid amide compound in the present invention is not particularly limited, it is preferably 5.0 mass% or less from the perspective of cost and productivity.
[0033] In the case where the propylene-based polymer according to the present invention contains the fatty acid amide compound, it is preferable that the number of carbon atoms of the fatty acid amide compound is 15 or more and 50 or less. Examples of fatty acid amide compounds having 15 or more and 50 or less carbon atoms include saturated fatty acid monoamide compounds, saturated fatty acid diamide compounds, unsaturated fatty acid monoamide compounds, and unsaturated fatty acid diamide compounds. In the present invention, the number of carbon atoms refers to the number of carbon atoms contained in a molecule. Specifically, fatty acid amide compounds include palmitamide, palmitoleamide, stearamide, oleamide, elaidicamide, vacenamide, linoleamide, linolenicamide, pinolenicamide, eleostearamide, stearidonicamide, boseopentaenoamide, arachidicamide, gadoleicamide, eicosenamide, eicosadienoamide, midicamide, eicosatrienoamide, arachidonicamide, eicosatetraenoamide, eicosapentaenoamide, heneicosylicamide, behenamide, erucicamide, docosadienoamide, adrenamide, osbondamide, glupanodonicamide, docosahexaenoamide, lignoceramide, nervonamide, tetracosapentaenoamide, nisinamide, seroticamide, Examples include montanamide, melisamide, ethylenebiscapricamide, ethylenebislauricamide, methylenebislauricamide, ethylenebisstearicamide, ethylenebisoleicamide, ethylenebishydroxystearicamide, ethylenebisbehenamide, ethylenebiserucamide, hexamethylenebisstearicamide, hexamethylenebisbehenamide, hexamethylenehydroxystearicamide, distearyladipamide, distearylsebamide, and hexamethylenebisoleicamide, and these may be used in combination.By making the carbon number of the fatty acid amide compound preferably 15 or more, more preferably 23 or more, and even more preferably 30 or more, the excessive precipitation of the fatty acid amide compound on the fiber surface is suppressed, thereby maintaining excellent spinnability and processing stability and high productivity. In addition, by making the carbon number of the fatty acid amide compound preferably 50 or less, more preferably 45 or less, and even more preferably 42 or less, the fatty acid amide compound is appropriately precipitated on the fiber surface, resulting in a laminated nonwoven fabric with excellent tactile properties. The carbon number of the fatty acid amide compound is preferably 15 to 50, more preferably 23 to 45, and even more preferably 30 to 42.
[0034] [Crunch Composite Fiber]
[0035] The crimped composite fiber according to the present invention is a composite fiber having a certain crimp. Examples of such crimped composite fibers include side-by-side type composite fibers and eccentric core-sheath type composite fibers.
[0036] Since the center of gravity of each component is separated in the cross-section of the staple fibers, when these composite fibers are released from tension during the spinning process, the fibers bend according to the difference in the amount of elastic recovery of each component, and crimp can be expressed as this continues in the direction of the fiber axis.
[0037] In the spunbond nonwoven fabric of the present invention, a side-by-side type composite fiber is preferred in which the distance between the center of gravity points that determine the crimp can be set large, from the perspective that the fiber can express fine crimp and improve bending flexibility.
[0038] The crimped composite fiber according to the present invention is composed of a first component having a propylene-based polymer as the main component and a second component having a propylene-based copolymer formed by copolymerizing an α-olefin, and the second component is disposed at the innermost side of the crimp in the cross-section of the crimped composite fiber.
[0039] The "innermost side of the crimp in the cross-section of the crimped composite fiber" referred to here is the location shown below, which will be explained using Fig. 1.
[0040] FIG. 1 is a schematic side view of a crimped composite fiber as seen when the crimped composite fiber according to the present invention is observed using a scanning electron microscope (SEM) or the like, where FIG. 1A is a side-by-side type composite fiber and FIG. 1B is a schematic side view of an eccentric core-sheath type composite fiber. The crimped composite fiber of the present invention is curved by a crimp, and an interface (B1) between a component (S1) and a component (S2) can be observed inside the fiber. At this time, the innermost component (S2) of the crimp, which is positioned on the inner side of the curved shape in the cross-section of the crimped composite fiber, is the component of the "innermost crimp in the cross-section of the crimped composite fiber" (second component) referred to in the present invention, and the outermost component (S1) of the crimp, which is positioned on the outer side of the curved shape, is the component of the "outermost crimp in the cross-section of the crimped composite fiber" (first component) referred to in the present invention.
[0041] In the case where the core component is completely covered by the sheath component in an eccentric core-sheath composite fiber, as shown in FIG. 1B, two interfaces (B1, B1'), namely the interface between component (S1) and component (S2) and the interface between component (S1') and component (S2), may be observed inside the fiber of the eccentric core-sheath composite fiber. In this case, a thin sheath component (S1') exists on the innermost surface of the crimp, but since the core component (S2) contracts more with respect to the sheath component (S1, S1') and bends S2 inward to form a crimp, the core component (S2) is made the innermost component (second component) of the crimp.
[0042] An important requirement of the crimped composite fiber according to the present invention is that a second component, mainly composed of a propylene copolymer formed by copolymerizing α-olefins, is disposed on the innermost side of the crimp.
[0043] Propylene-based copolymers formed by copolymerizing α-olefins have lower crystallinity compared to propylene homopolymers, so the amount of elastic recovery during crimping can be increased. For this reason, in the crimped composite fiber according to the present invention, the radius of curvature of the crimp shape can be reduced by placing the second component at the innermost part of the crimp, so the crimping can be finely controlled and the bending flexibility of the spunbond nonwoven fabric can be improved.
[0044] Examples of α-olefins that can be preferably used in the present invention include ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, and 4-methyl-1-hexene. In addition, it is also possible to use combinations of these. A copolymerization ratio of 0.5 mol% or more of these α-olefins can be cited as a preferred range. By setting the copolymerization ratio within this range, the amount of elastic recovery can be increased. On the other hand, while increasing the copolymerization ratio is desirable as it increases the amount of elastic recovery, if it is excessively increased, crystallinity is significantly reduced and spinning becomes unstable; therefore, it is preferable to set the copolymerization ratio to 20.0 mol% or less. More preferably, it is 0.5 to 20.0 mol%.
[0045] In the cross-section of the crimped composite fiber according to the present invention, the state in which the second component is positioned at the innermost side of the crimp can be evaluated, for example, by microscopic Raman spectroscopy. Since the second component according to the present invention is copolymerized with an α-olefin, a peak is detected in the Raman spectrum of the second component that is not present in the Raman spectrum of a propylene homopolymer. By utilizing this, the position of the second component within the crimped composite fiber can be determined. For example, in the case where ethylene is copolymerized, 730 cm⁻¹ -1 A Raman band characteristic of ethylene units can be observed in the vicinity. An example of a measurement method is shown below.
[0046] First, a crimped staple fiber (crimped composite fiber) is cut from a spunbond nonwoven fabric and placed on a slide glass to determine the curvature of the fiber. The side of the fiber is observed at a magnification that allows observation of a single staple fiber, and a Raman spectrum is measured using micro-Raman spectroscopy for the polymer component located at the innermost part of the crimp. At this time, it is desirable that the beam spot diameter of the measurement light be sufficiently small relative to the fiber diameter, for example, 1 μm to 2 μm is preferred. The component on the inner side of the crimp is determined by comparing the Raman spectrum obtained in this way with the Raman spectrum of the propylene homopolymer.
[0047] In addition, the crimped composite fiber according to the present invention has an orientation parameter (I2) of the second component of 5.0 or higher. By doing so, the amount of elastic recovery of the second component can be made more significant.
[0048] The orientation parameter of the second component mentioned here is measured by microscopic Raman spectroscopy. In the case of propylene-based polymers, at 810 cm⁻¹ -1 and 840 cm -1 It is known that the Raman band in the vicinity exhibits strong anisotropy with respect to the polarization of the incident light. For this reason, 810 cm -1 and 840 cm -1The molecular orientation can be evaluated from the intensity of nearby Raman bands.
[0049] The orientation parameter of this second component is measured by the method described below.
[0050] (1) A crimped composite fiber is taken from a spunbond nonwoven fabric and placed on a slide glass so that the curvature of the fiber can be determined.
[0051] (2) For the polymer component placed at the innermost part of the crimp of the crimped composite fiber, the beam spot diameter is sufficiently small relative to the fiber diameter, and the Raman spectrum is measured by incident light polarized parallel to the fiber axis.
[0052] (3) For the obtained Raman spectrum, 750 cm -1 ~900 cm -1 Perform peak fitting within the range of, and 800 cm -1 ~815 cm -1 The maximum intensity of the peak having a maximum point between I2 (810) , 840–855 cm -1 The maximum intensity of the peak having a maximum point between I2 (840) Calculate as.
[0053] (4) Using these values, I2 (840) I2 regarding (810) The ratio of (I2 (810) / I2 (840) Calculate )
[0054] (5) The same operation as (1) to (4) is performed on 10 different fibers, and the simple numerical average of the results is calculated and rounded to the second decimal place. This value is the orientation parameter (I2) of the second component.
[0055] The orientation parameter (I2) of the second component indicates that the higher the value, the higher the molecular orientation of the second component. Therefore, as I2 increases, the orientation of the second component placed inside the crimp is higher, and since the amount of elastic recovery can be increased, a finer crimp can be formed, and a spunbond nonwoven fabric with very good bending flexibility is obtained. From this perspective, it is more preferable to set I2 to 5.2 or higher, and particularly preferable to set it to 5.5 or higher. In addition, the upper limit of the orientation parameter is not specifically limited, but the limit that can be manufactured with propylene-based polymer fibers is at most about 8.0.
[0056] Meanwhile, in the crimped composite fiber according to the present invention, from the perspective of making the difference in the amount of elastic recovery of each component significant, it is preferable that the first component be a propylene homopolymer. Since the propylene homopolymer has high crystallinity, the amount of elastic recovery during the spinning process can be reduced, and strength can be improved.
[0057] In addition, in the crimped composite fiber according to the present invention, in order to increase the difference in the amount of elastic recovery of each component, it is preferable that the orientation parameter of the first component be 6.0 or lower. If the orientation parameter of the first component is within this range, it indicates that the orientation of the first component is sufficiently low, so the amount of elastic recovery can be limited to a small amount. On the other hand, since fiber strength decreases if the orientation parameter of the first component becomes significantly smaller, it is more preferable to make it 4.0 or higher.
[0058] The orientation parameter of the first component mentioned here is measured by the method described below.
[0059] (1) A crimped composite fiber is taken from a spunbond nonwoven fabric and placed on a slide glass so that the curvature of the fiber can be determined.
[0060] (2) For the polymer component placed on the outermost side of the crimp of the crimped composite fiber, the beam spot diameter is sufficiently small relative to the fiber diameter, and the Raman spectrum is measured by incident light polarized parallel to the fiber axis.
[0061] (3) For the obtained Raman spectrum, 750 cm -1 ~900 cm -1 Perform peak fitting within the range of, and 800 cm -1 ~815 cm -1 The maximum intensity of the peak having a maximum point between I1 (810) , 840–855 cm -1 The maximum intensity of the peak having a maximum point between I1 (840) Calculate as.
[0062] (4) Using these values, I1 (840) I1 regarding (810) The ratio of (I1 (810) / I1 (840) Calculate )
[0063] (5) The same operation as (1) to (4) is performed on 10 different fibers, and the simple numerical average of the results is calculated and rounded to the second decimal place. This value is the orientation parameter (I1) of the first component.
[0064] In the crimped composite fiber according to the present invention, it is preferable that the area ratio of the second component in the cross-section of the crimped composite fiber is 1% to 80%. If the area ratio of the second component is within this range, sufficient distance between centers of gravity can be secured, thereby enabling the formation of fine crimps. From the perspective of further expanding the distance between centers of gravity, it is more preferable that the area ratio of the second component be 50% or less, and particularly preferable that it be 40% or less. As for the lower limit, it is more preferable that it be 10% or more, and particularly preferable that it be 20% or more.
[0065] The cross-section of a fiber referred to here means the plane obtained by cutting the fiber in a plane perpendicular to the fiber length direction of the staple fiber.
[0066] The area ratio of the second component in the cross-section referred to here is calculated as follows.
[0067] Short fibers (crimped composite fibers) that are crimped from a spunbond nonwoven fabric (or a spunbond nonwoven layer in the case of a laminated nonwoven fabric) are cut out and embedded, and sections are prepared using a microtome to observe the cross-section of the short fibers and placed on a slide glass. Then, the fiber cross-section is observed using a microscope built into a Raman spectrometer equipped with a 100x objective lens, and microscopic Raman spectroscopic measurements are performed on the two components constituting the fiber cross-section. By comparing the obtained Raman spectrum with the Raman spectrum of the propylene-based copolymer constituting the second component that was measured in advance, the component with a matching spectrum is identified as the second component.
[0068] Then, the section used for the above measurement is photographed using a transmission microscope at a magnification that allows observation of the cross-section of a single single fiber. From the photographed SEM image, image analysis software (e.g., "WinROOF2015" manufactured by Shoji Mitani Co., Ltd.) is used to measure the cross-sectional area (Af) of the fiber and the area (A2) of the second component, and the area ratio of the second component is calculated by Equation 1.
[0069] (Area ratio of the second component) = 100 × A² / Af Equation (1)
[0070] The simple numerical average of the results obtained by performing the same operation on 20 different crimped composite fibers and rounding off the first decimal place is the area ratio of the second component in the cross-section referred to in the present invention.
[0071] In the crimped composite fiber according to the present invention, by achieving the above requirements, fine crimps that have not existed before can be formed. In addition, the spunbond nonwoven fabric composed of this fiber has excellent bending flexibility. In the crimped composite fiber according to the present invention, it is preferable that the number of crimps be 50 / 25 mm or more.
[0072] The number of folds referred to here is calculated as follows.
[0073] An image is taken of the surface of a spunbond nonwoven fabric using a scanning electron microscope (SEM) at a magnification that allows observation of at least 10 crimped composite fibers. Using the captured image, the external length of the crimped composite fibers within the measurement range is measured. The number of crimped composite fiber peaks and valleys present in the external length is counted, and the total number of peaks and valleys is divided by 2. The total number is converted into a number per 25 mm. The simple numerical average of the results obtained by performing the same operation on 20 different fibers and rounding to the first decimal place is the crimp number referred to in the present invention.
[0074] As the value of this crimp number increases, it indicates that the elongation of the crimped composite fiber is higher. When made into a spunbond nonwoven fabric, the fiber bracing between heat-set points can be suppressed, thereby improving bending flexibility. From this perspective, a crimp number of 80 fibers / 25 mm or more is more preferable, and 100 fibers / 25 mm or more can be cited as a particularly preferable range. Furthermore, since it varies depending on the fiber diameter of the crimped composite fiber, there is no specific upper limit set for the crimp number; however, for example, 1000 fibers / 25 mm or less is preferable, and 750 fibers / 25 mm or less is more preferable.
[0075] In addition, in the crimped composite fiber according to the present invention, it is preferable that the crimp diameter is 400 μm or less. The crimp diameter referred to in the present invention can be obtained as follows and is explained using FIG. 2.
[0076] FIG. 2 is a diagram illustrating a method for measuring the crimp diameter on a scanning electron microscope (SEM) image observing the surface of an example of a spunbond nonwoven fabric according to the present invention. In the same manner as the measurement of the number of crimps described above, an image of the surface of the spunbond nonwoven fabric is captured. Using the captured SEM image, a tangent line (L) is drawn that touches the crests (P1) and crests (P2) of two adjacent crimps for the crimped composite fibers within the measurement range. The vertical distance (D) from the valley (V) between P1 and P2 to the tangent line (L) is measured as an integer value with the unit being μm. The crimp diameter referred to in the present invention is the value obtained by calculating the simple numerical average of the results of performing the same operation on 20 different fibers and rounding off the first decimal place.
[0077] By controlling the crimp diameter to be small, the thickness of the spunbond nonwoven fabric can be reduced, thereby obtaining good flexibility. In this regard, it is more preferable that the crimp diameter be 300 μm or less.
[0078] In the crimped composite fiber according to the present invention, the fiber diameter is not particularly limited, but as the fiber diameter becomes finer, the radius of curvature of the crimp can be reduced and a fine crimp is obtained, so it is preferable to make it 25.0 μm or less. On the other hand, if the fiber diameter is excessively small, there is a concern that the strength may decrease, so it is more preferably 5.0 μm or more.
[0079] [Spunbond Nonwoven Fabric]
[0080] Since the spunbond nonwoven fabric of the present invention is composed of characteristic crimped composite fibers as described above, it has very good bending flexibility.
[0081] For this reason, it is desirable that the spunbond nonwoven fabric of the present invention have a stiffness of 0.50 mN·cm or less. By having the stiffness within this range, it is possible to achieve good bending flexibility suitable for use as a sanitary material.
[0082] In addition, the degree of stiffness in the present invention is measured in accordance with “6.7.3 41.5° cantilever method” of JIS L1913:2010 “General nonwoven fabric test method”.
[0083] In addition, when used as a sanitary material, it is preferable that the spunbond nonwoven fabric of the present invention has a tensile strength per unit area and weight of 0.40 (N / 5 cm) / (g / m²) or higher. If the strength of the nonwoven fabric is within this range, it can be made to withstand process passability when manufacturing paper diapers, etc., or use as a product.
[0084] In addition, the strength in the present invention is a value obtained by dividing the average of the tensile strength (strength when the sample breaks) in two orthogonal directions by the weight per unit area, by a tensile test with a gripping interval of at least 5 cm, conducted in accordance with “6.3.1 Standard Time” of “6.3 Tensile Strength and Elongation (ISO Method)” of JIS L1913:2010 “General Nonwoven Fabric Test Method”.
[0085] It is preferable that the spunbond nonwoven fabric of the present invention has a weight per unit area of 10 g / m² or more and 150 g / m² or less. By having a weight per unit area of 10 g / m² or more, the spunbond nonwoven fabric can be made into a thickness suitable for use as a sanitary material and can be made into a spunbond nonwoven fabric having mechanical strength suitable for practical use. On the other hand, by having a weight of 150 g / m² or less, more preferably 120 g / m² or less, and even more preferably 100 g / m² or less, it can be made into a spunbond nonwoven fabric with excellent breathability.
[0086] In addition, the weight per unit area (g / m²) of the spunbond nonwoven fabric in the present invention is measured in accordance with “6.2 Mass per unit area” of JIS L1913:2010 “Test method for general nonwoven fabrics”.
[0087] The spunbond nonwoven fabric of the present invention preferably has a thickness of 2.00 mm or less. By controlling the thickness within this range, good bending flexibility is obtained. In this regard, a thickness of 1.50 mm or less is more preferable. On the other hand, since reducing the thickness increases fiber density and impairs bending flexibility, it is preferable to make the thickness 0.01 mm or more.
[0088] In addition, the thickness of the spunbond nonwoven fabric in the present invention is not specifically limited, but refers to the thickness under no load measured, for example, by a shape measuring instrument (for example, "VR3050" manufactured by Keyence Co., Ltd.).
[0089] [Method for manufacturing spunbond nonwoven fabric]
[0090] Next, a preferred embodiment for manufacturing the spunbond nonwoven fabric of the present invention will be described in detail.
[0091] A method for manufacturing a spunbond nonwoven fabric according to the present invention is preferably a method of separately melting the first component and the second component, which has a melt viscosity at least 1.20 times higher than that of the first component, extruding a composite polymer from a composite spinneret, forming a crimp such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt to form the crimped composite fiber, and collecting the crimped composite fiber on a collection belt.
[0092] The spunbond method is a method for manufacturing a nonwoven fabric that generally requires a process of melting a thermoplastic resin, which is the raw material, spinning it from a spinneret, cooling and solidifying it to obtain a filament, stretching it by pulling it with an air pulling unit such as an ejector, collecting it on a moving collecting belt to form a nonwoven fiber web, and then heat-bonding it. In the spunbond nonwoven fabric of the present invention, by employing the spunbond method, molecular orientation is promoted by air pulling, and the fibers are firmly fixed to each other by heat bonding, thereby enabling the acquisition of sufficient strength for use as a sanitary material.
[0093] As a preferred composite spinneret used in the method for manufacturing a spunbond nonwoven fabric of the present invention, it is preferable to have a mechanism capable of forming a side-by-side composite cross-section or an eccentric core sheath composite cross-section. In addition, the shape of the discharge hole of the spinneret may be freely selected as long as it does not impair the effects of the present invention, but it is preferable to make it a round hole from the perspective of spinneret stability.
[0094] In the method for manufacturing a spunbond nonwoven fabric of the present invention, it is preferable to separately melt the first component and the second component, which has a melt viscosity at least 1.20 times higher than that of the first component, and to extrude them as a composite polymer from the aforementioned composite spinneret.
[0095] The melt viscosity referred to in this invention is a shear rate of 31.4s at the spinning temperature. -1 It refers to the melt viscosity at and is measured by the method described below.
[0096] (1) Using a rotary rheometer (e.g., UBM’s “Rheosol-G3000”), raise the temperature to a temperature equivalent to the radiation temperature.
[0097] (2) After melting the polymer between parallel plates of φ20 mm, the gap between the plates is set to 0.5 mm.
[0098] (3) 31.4 ㎭ / s -1 It applies deformation at this speed.
[0099] (4) Under the above conditions, the melt viscosity is measured in units of Pa·s.
[0100] Since the spunbond method is a manufacturing process in which extruded polymers are deformed at high speed while cooling, the molecular orientation of the manufactured fibers changes depending on the melt viscosity at high shear. In particular, in the manufacture of composite fibers, if there is a difference in melt viscosity at high shear between the components, high stress is applied to the high-viscosity component, thereby enabling a higher molecular orientation. In the present invention, this phenomenon is [addressed] at a shear rate of 31.4s -1 We discovered that it can be evaluated by comparing the melt viscosity of the city.
[0101] In the method for manufacturing a spunbond nonwoven fabric according to the present invention, it is preferable to have a ratio of the melt viscosity of the second component to the first component of 1.20 times or more, and more preferable to have a ratio of 1.30 times or more. By setting the ratio of melt viscosity within this range, it becomes possible to highly molecularly orient the second component, which is a preferred embodiment of the spunbond nonwoven fabric according to the present invention, thereby enabling the formation of finer crimps. Although it is preferable for the ratio of melt viscosity to be larger as the crimps become finer, if it is made excessively large, a large difference in deformation behavior between the components occurs, which causes yarn breakage; therefore, it is more preferable to have a ratio of 3.00 times or less.
[0102] In addition, in the method for manufacturing a spunbond nonwoven fabric according to the present invention, in order to increase the orientation of the second component and to improve extrusion stability, it is preferable to extrude a composite polymer in which the mass ratio of the first component and the second component is 20:80 to 99:1. Furthermore, from the perspective of being able to extrude stably by making the extrusion speed of each component equal during extrusion, it is more preferable to have the mass ratio of the first component and the second component be 50:50 to 90:10, and particularly preferable to have it be 40:60 to 80:20.
[0103] In addition, in the present invention, the spinning temperature is preferably set to be (Tm+10℃) or higher and (Tm+100℃) or lower, where Tm is the melting temperature of the component with the higher melting temperature among the first and second components. By keeping the spinning temperature within the above range, a stable molten state can be achieved, thereby obtaining excellent spinning stability.
[0104] The ejected filament is subsequently cooled. Methods for cooling the ejected filament include, for example, forcibly blowing cold air onto the filament, naturally cooling it at the ambient temperature surrounding the filament, and adjusting the distance between the spinneret and the air traction unit, or a combination of these methods may be adopted. Additionally, the cooling conditions may be appropriately adjusted and adopted by taking into account the discharge volume per single hole of the spinneret, the radiating temperature, and the ambient temperature.
[0105] Next, the cooled and solidified yarn is pulled and stretched by compressed air sprayed from an air pulling unit. Regarding the spinning speed, it is preferable to have a speed of 2000 m / min or higher, and more preferably 3000 m / min or higher. By setting the spinning speed to 2000 m / min or higher, high productivity is achieved, and the orientation crystallization of the fibers proceeds, allowing for the production of fibers with higher strength.
[0106] The yarns stretched by air traction in this manner are collected on a moving collection belt and then provided to a heat-bonding process after being sheeted.
[0107] At this time, in the method for manufacturing a spunbond nonwoven fabric according to the present invention, it is preferable to form the crimped composite fiber by developing a crimp such that a second component is placed at the innermost side of the crimp between the air traction unit and the collection belt. Since the distance between the fibers between the air traction unit and the collection belt is sufficiently large relative to the crimp size, the crimp can be developed without interference between the fibers, which is advantageous for forming fine crimps. Furthermore, by completing the crimp development before sheeting, the amount of deformation of the sheet can be reduced, thereby preventing a decrease in strength due to weight non-uniformity per unit area.
[0108] In the method for manufacturing a spunbond nonwoven fabric according to the present invention, as a method for integrating the sheets collected from the collection belt, methods such as a thermal embossing roll having a pattern (irregularity) formed on the surface of each of the upper and lower pairs of rolls, a thermal embossing roll formed by a combination of a roll having a flat (smooth) surface on one side and a roll having a pattern (irregularity) formed on the surface of the other side, and a thermal calender roll formed by a combination of an upper and lower pair of flat (smooth) rolls, or a method of welding the sheets by ultrasonic vibration of a horn may be employed.
[0109] In particular, when the sheets are integrated by heating and pressing them using the rolls described above, it is desirable because the mechanical strength of the spunbond nonwoven fabric increases as the nonwoven fabric layer is sufficiently bonded.
[0110] On the other hand, as a method for integrating the above sheets, there is also a so-called air-through method, which involves blowing heated air or nitrogen to fuse the sheets.
[0111] When the spunbond nonwoven fabric of the present invention is manufactured using this air-through method, it is desirable because it has a large volume and excellent tactile feel.
[0112] [Laminated Nonwoven Fabric]
[0113] The laminated nonwoven fabric of the present invention is preferably formed by laminating a spunbond nonwoven fabric layer made of the spunbond nonwoven fabric and at least one elastomer layer. By using the spunbond nonwoven fabric as a spunbond nonwoven fabric layer and laminating at least one elastomer layer thereon, excellent bending flexibility can be achieved by combining the low stiffness characteristic of the elastomer.
[0114] First, the elastomer of the laminated nonwoven fabric of the present invention refers to a polymer compound having hard segments and soft segments at room temperature. As a characteristic, it may be deformed by a weak force, but in the present invention, as an indicator of this, it is preferable that the bending modulus be 500 MPa or less. Furthermore, the bending modulus in the present invention is measured in accordance with JIS K7171:2016 “Plastics - Method for determining bending properties,” and evaluates the flexibility of the raw material itself. In the laminated nonwoven fabric of the present invention, high bending flexibility can be obtained by laminating an elastomer layer using such an elastomer.
[0115] In addition, from the perspective of productivity, it is desirable for the elastomer to be a thermoplastic resin. Since the elastomer is a thermoplastic resin, it becomes easier to control the shape of the fiber cross-section or surface. Furthermore, the thermoplastic resin constituting this elastomer layer refers to a polymer that exhibits thermoplastic properties when heated above its melting point, while being able to deform with weak force at room temperature. Specifically, examples include polyurethane-based elastomers, polypropylene-based elastomers, polyethylene-based elastomers, polyester-based elastomers, polystyrene-based elastomers, polybutadiene-based elastomers, etc.
[0116] Such thermoplastic resins may be of one type or may consist of multiple thermoplastic resins. Among these, the laminated nonwoven fabric of the present invention may be appropriately selected and used in consideration of adhesion to the spunbond nonwoven layer or its constituent fibers.
[0117] In the laminated nonwoven fabric of the present invention, the elastomer layer refers to a layer made of the elastomer, and its form may include a film shape, a fabric shape such as a woven fabric, a knitted fabric, or a nonwoven fabric, a sheet shape such as a composite material in which an elastomer resin is impregnated into a fabric, or a laminate thereof. Among these, a nonwoven fabric shape is preferred. A nonwoven fabric layer formed by folding and overlapping fibers can significantly reduce the second moment of area compared to a film. Therefore, by laminating a layer in which the elastomer layer is in the form of a nonwoven fabric, the bending flexibility of the laminated nonwoven fabric can be improved.
[0118] As for the form of such nonwoven fabric, it can be selected from known nonwoven fabrics such as spunbond nonwoven fabric, meltblown nonwoven fabric, and staple fiber nonwoven fabric, but spunbond nonwoven fabric and meltblown nonwoven fabric are preferred from the perspective of productivity.
[0119] As described above, the laminated nonwoven fabric of the present invention is formed by laminating a spunbond nonwoven fabric layer and at least one elastomer layer. That is, regarding the laminated configuration, if the spunbond nonwoven fabric layer is denoted as (S) and the elastomer layer as (E), for example, if there are two layers, it is (S) / (E) / (S), if there are three layers, it is (S) / (E) / (S), etc., if there are four layers, it is (S) / (E) / (E) / (S), etc., and if there are five layers, it is (S) / (E) / (S) / (E) / (S), etc. Among these, a form in which the spunbond nonwoven fabric layer is laminated on both the front and back surfaces of the elastomer layer, that is, a form such as (S) / (E) / (S) or (S) / (E) / (S) / (E) / (S), is more preferable. This laminated configuration is selected according to the purpose of use, etc.
[0120] In the laminated nonwoven fabric of the present invention, it is preferable that the spunbond nonwoven fabric layer and the elastomer layer are integrated. The integration referred to here means that the layers are joined by interlocking of fibers, fixation by components such as adhesives, or fusion of thermoplastic resins constituting each layer.
[0121] [Method for manufacturing laminated nonwoven fabric]
[0122] The method for manufacturing a laminated nonwoven fabric according to the present invention comprises the steps of: separately melting the first component and the second component having a melt viscosity at least 1.20 times higher than that of the first component; extruding a composite polymer from a composite spinneret; forming a crimped composite fiber by forming a crimp such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt; collecting the crimped composite fiber on a collection belt to form a spunbond nonwoven fabric layer; and laminating at least one elastomer layer. Furthermore, the step of forming the spunbond nonwoven fabric layer is the same as the method for manufacturing a spunbond nonwoven fabric.
[0123] Furthermore, the process of laminating at least one elastomer layer can specifically employ methods such as laminating an elastomer layer by continuously collecting it in-line on a spunbond nonwoven fabric layer formed on a collecting belt as described above using a conventional method including known methods, and then integrating it by heating and pressing, or methods such as laminating a spunbond nonwoven fabric layer and an elastomer layer obtained separately offline and then integrating them by heating and pressing. Among these, the method of laminating an elastomer layer by continuously collecting it in-line on a spunbond nonwoven fabric layer formed on a collecting belt and then integrating it by heating and pressing is preferred because it offers excellent productivity. Additionally, methods for integration may include interlocking fibers using a method such as needle punching, or bonding them using an adhesive.
[0124] One preferred embodiment of the method for manufacturing a laminated nonwoven fabric according to the present invention is to form the elastomer layer by the spunbond method. This is preferred because adopting the spunbond method results in a laminated nonwoven fabric with high strength.
[0125] In addition, as another preferred embodiment of the method for manufacturing the laminated nonwoven fabric of the present invention, the elastomer layer may be formed by a melt-blow method. This is because, by employing the melt-blow method, a sheet can be formed more stably compared to the spunbond method. Furthermore, since the fiber diameter can be made smaller than that of the spunbond method, there is an advantage that bending flexibility can be further improved.
[0126] In addition, the method for manufacturing the laminated nonwoven fabric of the present invention may be such that the spunbond nonwoven fabric layer and at least one elastomer layer are laminated, and any configuration of the number or combination of layers may be adopted depending on the purpose.
[0127] [Hygiene Materials]
[0128] The sanitary material of the present invention comprises at least a portion of the spunbond nonwoven fabric or the laminated nonwoven fabric, thereby obtaining excellent bending flexibility. Furthermore, the sanitary material of the present invention is used for health-related purposes, such as medical care and nursing, and is mainly a disposable item, such as paper diapers, sanitary pads, gauze, bandages, masks, gloves, adhesive bandages, etc., and includes constituent members thereof, such as the top sheet, back sheet, and side gather of a paper diaper.
[0129] Examples
[0130] Next, the present invention will be described in detail based on examples. However, the present invention is not limited to these examples. In addition, regarding the measurement of each physical property, unless otherwise specified, the measurement was performed based on the above method.
[0131] [measurement method]
[0132] (1) Identification of the innermost component of the curl
[0133] The "inVia" Raman spectrometer manufactured by RENISHAW was used as the measurement device. The measurement conditions were carried out as follows.
[0134] Beam spot diameter: 1㎛
[0135] Light source: 532 nm
[0136] Laser Power: 10 mW
[0137] Diffraction grating: Single 1800 gr / mm, 3000(-1) gr / mm
[0138] Slit: 65㎛
[0139] A crimped staple fiber (crimped composite fiber) was cut from a spunbond nonwoven fabric (or a spunbond nonwoven layer in the case of a laminated nonwoven fabric) and placed on a slide glass to determine the curvature of the fiber. Then, the fiber was observed from the side using a microscope built into a Raman spectrometer equipped with a 100x objective lens to observe a single staple fiber. Microscopic Raman spectroscopic measurements were performed on the component located on the inner side of the curvature as viewed from the side of the fiber. The component located on the innermost side of the crimp was identified by comparing the obtained Raman spectrum with the Raman spectrum of a propylene homopolymer measured in advance.
[0140] (2) Area ratio of the second component
[0141] Short fibers (crimped composite fibers) crimped from a spunbond nonwoven fabric (or spunbond nonwoven layer in the case of laminated nonwoven fabric) were cut and embedded. Sections were prepared using a microtome to observe the cross-section of the short fibers and placed on a slide glass. Then, the fiber cross-section was observed using a microscope built into a Raman spectrometer equipped with a 100x objective lens. Microscopic Raman spectroscopic measurements were performed on the two components constituting the fiber cross-section. By comparing the obtained Raman spectrum with the Raman spectrum of a propylene-based copolymer measured in advance, the component with a matching spectrum was identified as the second component.
[0142] Then, the section used for the above measurement was photographed using a transmission microscope at a magnification level that allows observation of the cross-section of a single single fiber. From the photographed SEM image, the cross-sectional area of the fiber (Af) and the area of the second component (A2) were measured using image analysis software ("WinROOF2015" manufactured by Shoji Mitani Co., Ltd.), and the area ratio of the second component was calculated by Equation 1.
[0143] (Area ratio of the second component) = 100 × A² / Af Equation (1)
[0144] The same operation was performed on 20 different crimped composite fibers, and the simple numerical average of the results was calculated and the value rounded to the first decimal place was taken as the area ratio of the second component in the cross-section.
[0145] (3) Orientation parameter
[0146] The "inVia" Raman spectrometer manufactured by RENISHAW was used as the measurement device. The measurement conditions were carried out as follows.
[0147] Measurement Mode: Microscopic Raman (Polarization Measurement)
[0148] Polarization direction: Parallel to the fiber axis
[0149] Beam spot diameter: 1㎛
[0150] Light source: 532 nm
[0151] Laser Power: 10 mW
[0152] Diffraction grating: Single 1800 gr / mm, 3000(-1) gr / mm
[0153] Slit: 65㎛
[0154] Short fibers crimped from a spunbond nonwoven fabric were cut and placed on a slide glass to determine the curvature of the fibers. Then, the crimped composite fibers were observed from the side of the fiber using a 50x objective lens. Raman spectroscopic measurements were performed on the polymer components located at the innermost and outermost points of the curvature when viewed from the side of the fiber. Based on the obtained Raman spectra, the orientation parameters of each component were measured as described above.
[0155] (4) Curved
[0156] The surface of the spunbond nonwoven fabric was photographed using a scanning electron microscope (SEM, "VHX6000" manufactured by Keyence Co., Ltd.) at a magnification that allows observation of 10 to 50 crests of the constituent crest composite fibers. However, if fewer than 10 crests could be identified within a 10 mm × 10 mm field of view, the number of crests of the fiber was considered to be 0. The number of crests and troughs of the fiber per 25 mm was counted, and the sum was divided by 2 to determine the number of crests of the fiber. Similarly, 20 different fibers were measured, and the value obtained by rounding the simple numerical average to the first decimal place was determined to be the number of crests per 25 mm.
[0157] (5) Weight per unit area
[0158] The weight per unit area was measured in accordance with "6.2 Mass per unit area" of JIS L1913:2010 "Test method for general nonwoven fabrics".
[0159] (6) Lecture
[0160] The stiffness was measured according to "6.7.3 41.5° cantilever method" of JIS L1913:2010 "General nonwoven fabric test method".
[0161] (7) Tensile strength per unit area per weight
[0162] Using a tensile testing machine (TENSILON UCT-100 manufactured by Orientec Co., Ltd.), measurements were taken in accordance with “6.3.1 Standard Time” of “6.3 Tensile Strength and Elongation (ISO Method)” of JIS L1913:2010 “Test Method for General Nonwoven Fabrics”. From the measured data, the tensile strength per unit area and weight was calculated by dividing the average of the tensile strengths in two orthogonal directions (strength when the sample breaks) by the weight per unit area.
[0163] [Example 1]
[0164] As the first component, the shear rate is 31.4s -1 Homopolypropylene having a melt viscosity of 153 Pa·s (hereinafter referred to as "HomoPP," including in Table 1, etc.) was used, and as the second component, a shear rate of 31.4s -1Ethylene copolymerized polypropylene (hereinafter referred to as "coPP," including in Table 1) obtained by copolymerizing 2.7 mol% of ethylene having a melt viscosity of 270 Pa·s was used. These were melted in a separate extruder and extruded at a spinning temperature of 230°C from a rectangular die that produces a side-by-side composite cross-section, with an extrusion amount of 0.55 g / (min·hole) per hole and an extrusion mass ratio of component 1:component 2 = 50:50. After cooling and solidifying the extruded fibers, they were pulled and stretched by compressed air with an ejector pressure of 0.10 MPa in a rectangular ejector and collected on a moving collection belt to obtain a nonwoven fiber web. At this time, the fibers in the nonwoven fiber web had fine crimps. The nonwoven fiber web obtained in this manner was integrated by using a metal embossing roll having a pair of upper and lower heating mechanisms, consisting of a metal flat roll on the upper roll and a metal embossing roll on the lower roll, with a linear pressure of 300 N / cm and a surface temperature of 125°C of the embossing roll, to obtain a spunbond nonwoven fabric with a weight per unit area of 20 g / m². The innermost crimp component, orientation parameter, number of crimps, weight per unit area, stiffness, and tensile strength of the obtained spunbond nonwoven fabric were evaluated. The results are shown in Table 1.
[0165] [Example 2]
[0166] As the first component, the shear rate is 31.4s -1 A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that homoPP with a melt viscosity of 220 Pa·s was used. For the obtained spunbond nonwoven fabric, the innermost crimp component, orientation parameter, number of crimps, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 1.
[0167] [Example 3]
[0168] A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that the extrusion mass ratio was Component 1:Component 2 = 80:20. For the obtained spunbond nonwoven fabric, the innermost crimp component, orientation parameter, number of crimps, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 1.
[0169] [Example 4]
[0170] As the second component, the shear rate is 31.4s -1 A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that ethylene copolymerized polypropylene with 5.3 mol% ethylene and a melt viscosity of 280 Pa·s was used. For the obtained spunbond nonwoven fabric, the innermost crimp component, orientation parameter, number of crimps, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 1.
[0171] [Example 5]
[0172] A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that the extrusion mass ratio was Component 1:Component 2 = 99:1. For the obtained spunbond nonwoven fabric, the innermost crimp component, orientation parameter, number of crimps, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 1.
[0173] [Comparative Example 1]
[0174] As the first component, the shear rate is 31.4s -1 A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that homoPP with a melt viscosity of 280 Pa·s was used.
[0175] [Comparative Example 2]
[0176] As the second component, the shear rate is 31.4s -1 A spunbond nonwoven fabric was obtained in the same manner as in Example 1, except that homoPP with a melt viscosity of 270 Pa·s was used.
[0177]
[0178] As shown in Table 1, it can be seen that the spunbond nonwoven fabrics of Examples 1 to 4 exhibit excellent bending flexibility and strength. In particular, Examples 1, 3, and 4 showed very excellent bending flexibility. On the other hand, for the nonwoven fabrics of Comparative Examples 1 and 2, the bending flexibility was low because the crimping of the fibers on the surface of the spunbond nonwoven fabric was loose.
[0179] [Example 6]
[0180] (Spunbond nonwoven layer)
[0181] Shear rate 31.4s as the first component -1 Homopolypropylene having a melt viscosity of 153 Pa·s is used, and as the second component, a shear rate of 31.4s -1 Ethylene copolymerized polypropylene, copolymerized with 2.7 mol% ethylene and having a melt viscosity of 270 Pa·s, was used. These were melted in a separate extruder and extruded at a spinning temperature of 230°C from a rectangular die that produces a side-by-side composite cross-section, with an extrusion amount of 0.55 g / (min·hole) per hole and an extrusion mass ratio of component 1:component 2 = 50:50. After cooling and solidifying the extruded yarn shape, it was pulled and stretched by compressed air with an ejector pressure of 0.10 MPa in a rectangular ejector and collected on a moving collection belt to obtain a spunbond nonwoven fabric layer with a weight of 10 g / m² per unit area (indicated as "PP / coPP-SB" in Table 2). At this time, the fibers within the spunbond nonwoven fabric layer had fine crimps.
[0182] (Elastomer layer)
[0183] An elastomer layer was formed by the spunbond method using a polypropylene-based elastomer copolymerized at 15 wt% with a melt viscosity of 423 Pa·s and a bending modulus of 13 MPa (indicated as "PP-based" in Table 2). Specifically, the polypropylene-based elastomer with a melt viscosity of 423 Pa·s was melted in an extruder, and the spinning temperature was set to 230°C. The elastomer was then extruded from a rectangular die with an extrusion rate of 0.20 g / (min·hole) per single hole. After cooling and solidifying the extruded filament, it was pulled and stretched by compressed air with an ejector pressure of 0.10 MPa in a rectangular ejector and collected on a moving collection belt to obtain an elastomer layer (spunbond method) with a weight of 30 g / m² per unit area.
[0184] (Laminated nonwoven fabric)
[0185] An elastomer layer is encapsulated on the spunbond nonwoven layer obtained above by the method described above, and a spunbond nonwoven layer identical to the spunbond nonwoven layer is encapsulated thereon, and the nonwoven layers are laminated under the same pressurization and heating conditions as in Example 1 to form a three-layer structure of spunbond nonwoven layer - elastomer layer (spunbond method) - spunbond nonwoven layer (regarding the laminated configuration, S / E in Table 2). S1 A laminated nonwoven fabric (indicated as / S) was obtained. For the obtained laminated nonwoven fabric, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 2.
[0186] [Example 7]
[0187] Except for the elastomer layer being produced by the melt-blow method as follows, a three-layer structure of spunbond nonwoven fabric layer - elastomer layer (melt-blow method) - spunbond nonwoven fabric layer is prepared in the same manner as Example 6 (regarding the laminated configuration, S / E in Table 2 M A laminated nonwoven fabric (indicated as / S) was obtained. The weight per unit area, stiffness, and tensile strength of the obtained laminated nonwoven fabric were evaluated. The results are shown in Table 2.
[0188] (Elastomer layer)
[0189] A polypropylene-based elastomer with a melt viscosity of 423 Pa·s and a bending modulus of 13 MPa was melted in an extruder, and after being extruded at a spinning temperature of 255°C, a hole diameter φ of 0.25 mm, and a single hole discharge rate of 0.12 g / (min·hole), air was injected under conditions of a temperature of 275°C and a pressure of 0.15 MPa to obtain an elastomer layer (meltblow method) with a weight of 30 g / m² per unit area.
[0190] [Example 8]
[0191] A laminated nonwoven fabric was obtained in the same manner as in Example 6, except that as the elastomer layer, a film having a weight of 30 g / m² per unit area made of the polypropylene-based elastomer used in Example 6 was used (regarding the laminated composition, S / E in Table 2 F (Indicated as / S). For the obtained laminated nonwoven fabric, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 2.
[0192] [Example 9]
[0193] A laminated nonwoven fabric was obtained in the same manner as in Example 6, except that a polyethylene-based elastomer with a melt viscosity of 252 Pa·s and a bending modulus of 23 MPa (indicated as PE-based in Table 2) was used for the elastomer layer (regarding the laminated composition, S / E in Table 2). S2 (Indicated as / S). For the obtained laminated nonwoven fabric, weight per unit area, stiffness, and tensile strength were evaluated. The results are shown in Table 2.
[0194] [Reference Example 1]
[0195] A laminated nonwoven fabric was obtained in the same manner as in Example 6, except that the elastomer layer was replaced with a conventional spunbond nonwoven layer (not an elastomer layer) as shown below (the laminated composition is indicated as S / S / S in Table 2). The weight per unit area, stiffness, and tensile strength of the obtained laminated nonwoven fabric were evaluated. The results are shown in Table 2.
[0196] (Spunbond nonwoven layer)
[0197] Non-elastomer homopolypropylene with a melt viscosity of 290 Pa·s and a bending modulus of 1550 MPa was melted in an extruder, and the material was extruded from a rectangular die at a single hole discharge rate of 0.45 g / (min·hole) at a spinning temperature of 230°C. After cooling and solidifying the extruded filament, it was pulled and stretched by compressed air with an ejector pressure of 0.10 MPa in a rectangular ejector, and collected on a moving collection belt to obtain a spunbond nonwoven fabric layer with a weight of 30 g / m² per unit area.
[0198]
[0199] As shown in Table 2, it can be seen that the laminated nonwoven fabrics of Examples 6 to 9 have excellent bending flexibility and strength. On the other hand, for the nonwoven fabric of Reference Example 1, the result was that the bending flexibility of the laminated nonwoven fabric was low because the spunbond nonwoven layer laminated between the spunbond nonwoven layers was rigid. Explanation of the symbols
[0200] S1: Ingredients S1': Component S2: Ingredients B1: Interface B1': Interface P1, P2: Mountain of the Curved Axis L: Tangent line between P1 and P2 V: The groove between P1 and P2 D: Perpendicular distance from the valley (V) between P1 and P2 to the tangent (L).
Claims
Claim 1 A spunbond nonwoven fabric composed of a crimped composite fiber comprising a first component having a propylene-based polymer as the main component and a second component having a propylene-based copolymer formed by copolymerizing an α-olefin, wherein in the cross-section of the crimped composite fiber, the second component is disposed at the innermost side of the crimp, the orientation parameter (I2) of the second component is 5.0 or higher, and the propylene-based polymer of the first component is a propylene homopolymer. Claim 2 A spunbond nonwoven fabric according to claim 1, wherein the orientation parameter (I1) of the first component is 6.0 or less. Claim 3 A spunbond nonwoven fabric according to claim 1 or 2, wherein the area ratio of the second component in the cross-section of the crimped composite fiber is 1% to 80%. Claim 4 A spunbond nonwoven fabric according to claim 1 or 2, wherein the number of crimps of the crimped composite fibers observed on the surface of the nonwoven fabric is 50 / 25 mm or more. Claim 5 A laminated nonwoven fabric comprising a spunbond nonwoven fabric layer made of the spunbond nonwoven fabric described in claim 1 and at least one elastomer layer laminated thereon. Claim 6 In claim 5, the laminated nonwoven fabric in which the elastomer layer is a layer made of an elastomer nonwoven fabric. Claim 7 A sanitary material comprising at least a portion of the spunbond nonwoven fabric described in claim 1, or the laminated nonwoven fabric described in claim 5 or 6. Claim 8 A method for manufacturing a spunbond nonwoven fabric according to claim 1 or 2, wherein the first component and the second component, having a melt viscosity at least 1.20 times higher than the melt viscosity of the first component, are melted separately, a composite polymer is extruded from a composite spinneret, and then a crimp is formed such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt to form the crimped composite fiber, and the crimped composite fiber is collected on a collection belt. Claim 9 A method for manufacturing a spunbond nonwoven fabric according to claim 8, wherein a composite polymer having a mass ratio of the first component and the second component of 20:80 to 99:1 is extruded. Claim 10 A method for manufacturing a laminated nonwoven fabric according to claim 5 or 6, comprising the steps of: separately melting the first component and the second component having a melt viscosity at least 1.20 times higher than the melt viscosity of the first component; extruding a composite polymer from a composite spinneret; forming a crimped composite fiber by forming a crimp such that the second component is positioned at the innermost side of the crimp between an air traction unit and a collection belt; collecting the crimped composite fiber on a collection belt to form a spunbond nonwoven fabric layer; and laminating at least one elastomer layer. Claim 11 In claim 10, a method for manufacturing a laminated nonwoven fabric in which the elastomer layer is formed by the spunbond method. Claim 12 In claim 10, a method for manufacturing a laminated nonwoven fabric in which the elastomer layer is formed by a melt-blow method.
Citation Information
Patent Citations
Filament-laminated spun-bonded nonwoven fabric
JP1995197367A
Crimped conjugate fiber and method for producing the same
JP2008133572A
Composite fibers with low-temperature processability, nonwoven fabrics and molded articles using the same.
JP2011506778A
Spun-bonded nonwoven fabric and method for producing same
WO2018092444A1
